Residue-derived carbon transformations with altered residue management in an irrigated corn system in Colorado - Leichty, Sarah I., author; Cotrufo, M. Francesca, advisor; Stewart, Catherine, advisor; Conant, Richard, committee member (Colorado State University. Libraries, 2019)
Soil plays an essential role in storing carbon (C) and nutrients regulating climate and sustaining food production. As such, it is important to understand how human activities affect C cycling in soil. Agricultural lands, particularly croplands, comprise some of the most managed areas of the world. We have the potential to positively impact C sequestration in croplands by understanding how residue management affects the C mineralization as well as the formation and stabilization of soil organic C (SOC). No-till (NT), which leaves residue on the surface, has been proposed as the superior residue management for building SOC due to a decreased rate of residue and existing SOC decomposition. Conventional tillage (CT), which breaks aggregates while incorporating residue into the soil, is thought to result in less SOC storage through increased residue and SOC decomposition, and soil erosion. However, NT does not always result in higher SOC storage than CT when measuring total profile stocks and the gains might not be stable in a changing climate. I studied a semi-arid, irrigated, corn system where gains in surface SOC but losses at depth had been observed because of conversion to NT. I studied the effect of altered residue management by mimicking NT and CT residue placement and soil disturbance and followed the residue-derived C into soil respiration (CO2) and physically defined SOC pools. I applied isotopically labeled (13C) residue either on the soil surface (NT) or incorporated into the soil (CT), which allowed me to track losses and transformations of residue C under different residue placement. A third treatment with surface-applied residue following soil disturbance tested the effect of disturbing aggregates during tillage. I collected soil respiration measurements and determined its isotopic composition for twelve months following residue addition to understand how residue location and soil disturbance affected the rate of total CO2 efflux, and of their component fractions (i.e., derived from residue vs. derived from soil). As reported in Chapter 2, I found that incorporated residue had higher residue-derived respiration in the first six months ("off season"), but surface-applied residue had higher residue-derived respiration during the later six months ("growing season"). Growing season respiration rates were higher and driven largely by warmer temperature and more available water (i.e. irrigation events) than in the off season. Thus, the growing season trend dictated the full year trend with surface residue more vulnerable to loss as CO2 efflux compared to incorporated residue that was likely protected from decomposition by the soil matrix presumably from either aggregation or mineral associations. Following, I tracked the fate of the remaining residue C by measuring SOC pools with varying levels of stability and report these results in Chapter 3. I harvested incorporated and surface-applied residue treatments six months after residue addition. I found that incorporated residue had more residue-derived C in bulk soil compared to surface-applied residue treatments. The larger pool of residue SOC within the incorporated residue treatment was due to increased residue decomposition compared to slower surface residue decomposition. Based on the two pathways of SOC formation proposed in Cotrufo et al., (2015a), residue C was tracked into both minerally-associated and particulate organic matter (MAOM and POM respectively). We hypothesized more MAOM formation due to the importance of the DOC-microbial pathway at the initial stages of decomposition with a smaller pool of POM due to the physical transfer path becoming important later in decomposition. After six months of residue decomposition, residue C was greater in POM than MAOM fractions for all treatments (either marginally or significantly), indicating the importance of POM formation pathways in both surface-applied and incorporated residue treatments. After accounting for differences in decomposition, I found that incorporated and surface-applied SOC formation efficiencies of residue decomposition (i.e., the fraction of residue C decomposed that resulted in SOC versus being lost through mineralization) were similar when SOC pools were summed. However, the SOC formation efficiency of surface-applied residue with soil disturbance was 40% lower than either surface-applied or incorporated residue, indicating that soil disturbance inhibited SOC formation when residue was surface applied. It is surprising that surface-applied residue POM formation was high in the short term because surface residue had to enter the soil matrix over time unlike incorporated residue. The high amount of POM likely formed through biotic transformation by soil fauna in contrast to POM protection likely through aggregation in the incorporated residue treatment. Thus, it appears that POM formation was more important than MAOM formation for both surface-applied and incorporated residue management. My results show that intact NT systems, particularly with earthworms and fungal networks may efficiently transfer POM C belowground during the initial six months of decomposition. At 12 months, I predict that protection of incorporated residue will be more pronounced compared to surface residue, since surface residue appears to be vulnerable to decomposition after irrigation events. Longer-term results (~3 years) will elucidate whether CT residue management continues to store more residue SOC than NT, potentially explaining why irrigated, NT systems might not consistently store more SOC. Climate change will likely increase the use of irrigation to meet crop water needs, thus we need to continue exploring the complexities of SOC formation and stabilization within irrigated NT and CT in order to sequester C for the health of our soil and planet.
Keywords: soil carbon; soil organic matter; tillage; soil health; irrigation; stable isotopes